IMPLEMENTATION OF THE SOROGAN METHOD, IN IMPROVING THE ABILITY TO READ THE YELLOW BOOK - Permana, Muharirul Umam Adi; Jazilurrahman, Jazilurrahman; Mudarris, Badrul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyze the Implementation of the Sorogan Method in Improving the Reading Ability of Grade XII Students of the Yellow Book of Madrasah Aliyah Nurul Jadid Paiton Probolinggo Religious Program. In addition, the researcher will explore the factors that affect the effectiveness of the sorogan method in increasing students' understanding of the yellow book and identify the challenges faced in the application of this method. To obtain data from the research results, research is carried out using a qualitative approach with the type of case study research. This research was carried out at Madrasah Aliyah Nurul Jadid, from November 26, 2024 to December 26, 2024. Data collection techniques are carried out using field observation, interviews, and documentation. Data analysis, the researcher uses qualitative descriptive analysis, namely through: Data display, Data reduction, Drawing conclusions. The results shown from the research on the Implementation of the Sorogan Method in Improving the Reading Ability of Grade XII Students of the Yellow Book of Madrasah Aliyah Nurul Jadid Religious Program Paiton Probolinggo are that there are stages that are seen and applied by teachers or teachers, namely students start with (individual learning), teachers start learning, students read the material, teachers start reading and close learning. The Supporting Factors are learning discussions, learning motivation encouragement and seminars. And the inhibiting factors are Non-Effective Discussions, Limited Book References, Lack of Time Management, and Lack of Daily Mutholaah.